2023
DOI: 10.7461/jcen.2023.e2023.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mechanical thrombectomy for acute ischemic stroke on weekdays versus nights/ weekends in a Japanese primary stroke core center

Abstract: Objective: The term “weekend effect” refers to an increase in the mortality rate for hospitalizations occurring on weekends versus weekdays. In this study, we investigated whether such an effect exists in patients undergoing mechanical thrombectomy for acute ischemic stroke with large vessel occlusion (currently the standard treatment for this condition) at a single center in Japan.Methods: We surveyed 151 patients who underwent mechanical thrombectomy for acute ischemic stroke with large vessel occlusion (75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Mpotsaris et al reported that the patients admitted during nighttime and weekends showed statistically prolonged door-to-reperfusion times; however, it did not affect the rate of revascularization and favorable outcome ( 12 ). This main conclusion was also supported by similar studies by Potts et al ( 8 ), Lin et al ( 9 ), and Omura et al ( 10 ).. They explained that the outpatient clinics did not provide services, which led to the patients being crowded into the emergency department during non-working hours, and subsequently slightly increased door-to-image times.…”
Section: Discussionsupporting
confidence: 64%
“…Mpotsaris et al reported that the patients admitted during nighttime and weekends showed statistically prolonged door-to-reperfusion times; however, it did not affect the rate of revascularization and favorable outcome ( 12 ). This main conclusion was also supported by similar studies by Potts et al ( 8 ), Lin et al ( 9 ), and Omura et al ( 10 ).. They explained that the outpatient clinics did not provide services, which led to the patients being crowded into the emergency department during non-working hours, and subsequently slightly increased door-to-image times.…”
Section: Discussionsupporting
confidence: 64%